Mok Wei Wei works by W Architects - Mok, Wei Wei 1956- (Thames & Hudson, 2020)
During a career spanning over three decades, award-winning architect Mok Wei Wei has designed numerous large- and small-scale projects in Singapore with his practice W Architects. From apartment complexes and museums to houses and community centres, each project reveals the architect's key inspirations and ingenious solutions to the challenges of building in the tropical city-stage. The works are presented in three themed chapters - Refract, Respond, Reflect - and move through Mok Wei Wei's career from the early 1980s to the present. In our increasingly urban world, W Architects illustrates a unique approach to designing buildings for a dense city environment, working in the context of a diverse multicultural society facing up to the challenges of climate, heritage preservation, globalism and national identity